Parliamentary assertion and deep integration: the European parliament in the CETA and TTIP negotiations1. Issue 5 (3rd September 2017) - Roederer-Rynning, Christilla
Abstract: Scholars have long viewed parliamentarians as parochial actors having little interest, or incentive to engage, in international diplomacy. Yet, parliaments have recently taken on a very active role in various international negotiations. This article explores the role of the European Parliament (EP) in the European Union (EU)–Canada Comprehensive Economic and Trade Agreement (CETA) and the EU–United States Transatlantic Trade and Investment Partnership (TTIP) negotiations. Drawing on classic institutionalist insights, it develops the concept of parliamentary assertion and explores its usefulness through a combination of comparative and process-tracing analyses. The conclusions are threefold: (1) the EP has asserted its power in international trade matters beyond the simple power of consent; (2) the EP's search for legitimacy in the EU polity is driving this phenomenon; and (3) this phenomenon is significant beyond the current CETA and TTIP negotiations.